The Founding Fathers reconsidered - Bernstein, Richard B., 1956- (Oxford ; New York : Oxford University Press, 2009)
"This concise study reintroduces us to the history that shaped the founding fathers, the history that they made, and what history has made of them. It gives the reader a context within which to explore the world of the founding fathers and their complex and still-controversial achievements and legacies"--Provided by publisher.
American Window
Includes bibliographical references and index.
Keywords: Founding Fathers of the United States; Founding Fathers of the United States -- Historiography; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.